Predictors of Physical Activity in Patients With Fibromyalgia: A Path Analysis. Issue 1 (17th December 2020) - Kaleth, Anthony S.; Bigatti, Silvia M.; Slaven, James E.; Kelly, Nicholas; Ang, Dennis C.
Abstract : Background/Objective: The aim of this study was to identify psychological factors that influence moderate-vigorous physical activity (MVPA) participation in patients with fibromyalgia. Methods: In this secondary data analysis, 170 patients received personalized exercise plans and completed baseline and follow-up assessments of self-reported physical activity at weeks 12, 24, and 36. Structural equation modeling was used to examine the predictive strengths of psychological factors (exercise self-efficacy, perceived barriers, and intention) on MVPA participation. Results: Using a threshold increase in MVPA of 10 or greater metabolic equivalent hours per week (MET h/wk), 3 groups were defined based on subjects who achieved a minimum increase of 10 MET h/wk that was sustained for at least 12 weeks (SUS-PA), achieved an increase of 10 MET h/wk that was not sustained for at least 12 weeks (UNSUS-PA), and did not achieve an increase of 10 MET h/wk (LO-PA). Increases in exercise self-efficacy and intention and reductions in perceived barriers were associated with increased volume of PA, showing the greatest change in the SUS-PA, followed by UNSUS-PA. For the LO-PA group, there was no change in exercise self-efficacy, a decrease in intention, and an increase in barriers. Using path analysis, exercise self-efficacy and perceived barriers were associated with higher volumes of physical activity via greater intention to engage in MVPA. Conclusions: For patients with fibromyalgia, exercise self-efficacy, perceived barriers, and intention to exercise are important constructs for increasing physical activity. Our findings provide guidance for practitioners who seek to promote physical activity in fibromyalgia and suggestions for researchers aiming to improve prediction models.